Combination of low-dose rituximab, bortezomib and dexamethasone for the treatment of autoimmune hemolytic anemia. Issue 4 (28th January 2022) - Yao, Mingkang; Zhang, Jingjing; Li, Ying; Lv, Linlin; Jia, Lu; Yang, Chunyan; Huang, Yu; Liu, Haihui; Wang, Jian; Chen, Mingtai; Zhang, Hao
Abstract : Abstract: Autoimmune hemolytic anemia (AIHA) therapy may be associated with severe complications such as diabetes, hypertension, obesity, osteoporosis, peptic ulcers, infection, and some other diseases. To reduce those effects, we used low-dose rituximab, bortezomib and dexamethasone (LowR-BD regimen) to treat AIHA. The purpose of this study was to evaluate the efficacy and safety of this regimen. Seven patients with warm AIHA (wAIHA) admitted from March 2020 to October 2020 were treated with LowR-BD regimen: Rituximab 100 mg by intravenous infusion on day 1 combined with bortezomib 1.3 mg/m 2 by subcutaneous injection on day 2 plus dexamethasone 20 mg by intravenous infusion on days 2, 3. Clinical efficacy and safety were assessed at the regular reexamination of relevant indicators and follow-up. After 4 cycles of the LowR-BD regimen, the overall response rate (ORR) was 85.71% with a complete response (CR) of 28.57% and a partial response (PR) of 57.14%. After a median follow-up of 12 (range 7–13) months, 5 patients achieved CR and 2 patients had PR status, including 1 patient who did not respond to LowR-BD treatment and reached CR after using methylprednisolone combined with cyclophosphamide. One patient relapsed and achieved PR after retreatment of 2 cycles LowR-BD regimen. The patients tolerated the treatment well and did not complain of apparently adverse reactions except a patient with Sjogren's syndrome and bronchiectasis who developed a severe infection during treatment. Low-dose rituximab combined with bortezomib and dexamethasone is effective and relatively safe in patients with wAIHA.